Virtuelle und hybride Fremdsprachenlehre (Frank & Timme, 2023)
Virtual and hybrid teaching: what has been a stopgap solution for many in recent years is becoming increasingly important for foreign language teaching today. This book presents current developments in digitised language teaching and provides an outlook on its future. The authors offer a comprehensive overview of teaching concepts for virtual and hybrid teaching. They also present concrete suggestions and numerous tried-and-tested examples for practical application. The focus is on the role of the teacher in the learning process. A commentary on the use of chatbots, such as ChatGPT, in teaching picks up the debate on the topic of artificial intelligence and sheds light on its relevance for language teaching.